Determination of Haemaglutinin and Gene Encoding Fibronectin Binding Proteins Staphylococcus aureus Isolated from Dairy Milk Cows - Pratomo, Feny Prabawati; Salasia, Siti Isrina Oktavia; Tato, Syarifudin (Indonesian Journal of Biotechnology, 2011)
AbstractStaphylococcus aureus is a major pathogen causing clinical and subclinical mastitis in dairy milk cows. The mastitis has immense economical impacts, where it reduces of the quantity and quality of milk production. The aims of the research were to analyse haemaglutinin and gene encoding fibronectin binding proteins. Nineteen Staphylococcus aureus isolates used in the present study were isolated from dairy milk cows from Yogyakarta, Solo, Boyolali and Sumedang. The haemagluitinin of S. aureus were determined based on haemaglutination reaction to erythrocytes of rabbit. Detection of gene encoding fibronectin binding proteins could be performed with specific primers using polymerase chain reaction (PCR). The results of studies showed that most of S. aureus (78,95%) expressed haemaglutinin based on their ability to aglutinate rabbit erythrocytes. Analysis of gene encoding fibronectin binding proteins of S. aureus revealed gene fnbA with size of approximately 1300 bp for 57,89% isolates, gene fnbB with size of approximately 900 bp for 31,58% isolates and both of gene fnbA and fnbB could be detected for 31,58% isolates. The characters of S. aureus based on haemaglutinin, gene fnbA and fnbB of the present study could be used as an information to control of S. aureus infection in dairy herds.Keywords : Staphylococcus aureus, haemaglutinin, gene encoding fibronectin binding protein, milk cow